High-Fidelity Surgical Middle Ear Simulator: A Pilot Study. Issue 8 (September 2021) - Shim, Timothy; Chillakuru, Yeshwant; Darwish, Christina; Sparks, Andrew; Kim, Sunny; Wiedermann, Joshua; Monfared, Ashkan
Abstract : Objectives: To assess a middle ear simulator as a surgical training tool among a cohort of novice trainees. Study Design: Prospective pilot study. Setting: The George Washington University Hospital (tertiary care academic hospital). Participants: Twenty one medical students and physician assistant students completed the protocol. Each student produced four recordings over 10 attempts. The two raters were attending surgeons from the George Washington University Hospital. Interventions: Stapedotomies performed on a high-fidelity middle ear simulator. Participants were assessed at baseline with a Purdue pegboard test and trained with video and a low fidelity middle ear simulator. Main Outcome Measures: Two experts rated recordings on scales based upon a validated objective skills assessment test (OSAT) format. Results: Inter-rater reliability was strong across all stapedotomy skills scores and global rating scores. Participants demonstrated statistically significant improvement up to the third recording (seventh attempt), but the scores on the fourth recording (tenth attempt) were not significantly different from the third. One participant failed to improve in score over 10 attempts. Pegboard test performance was not correlated with score improvement. Low-fidelity trial time was significantly correlated to stapedotomy and global rating scores. Conclusions: This pilot study serves as the first investigation of this middle ear simulator amongst a cohort of trainees. A high-fidelity middle ear simulator may serve as a measurement tool to select future surgical trainees, customize training pathways, and assess surgical capacity before graduation.